IoT-Based Mining Safety and Air Quality System - Chaitanya, A.; Rahul, P.; Siddhartha , A.; Dholvan, Mohan (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2023)
Industrial safety is a major issue for the mining sector. Healthcare and effective communication are crucial for worker safety and productivity. Reliable communication is vital for monitoring possible threats and responding to them, while medical personnel protection equipment and examinations are essential. Given that the current safety systems are inadequate, the mining industry must enhance its safety measures. The mining sector uses safety systems like ventilation, emergency response plans, and gas monitoring to reduce risks and protect workers. Ventilation provides clean air, gas monitoring identifies hazardous gases, and emergency action protocols lessen accidents. These systems have shortcomings, such as a limited ability to prevent accidents, an insufficient airflow, and an inability to detect all gases. As a result, these systems require improvement. Our solution raises safety in the mining sector by boosting communication and utilizing the IoT (Internet of Things) to monitor air quality, toxicity, and miners’ vital signs. Sensors, an esp32 board, and the blynk software enable real-time monitoring and reporting of risks. In addition to ensuring the health of the workforce, this strategy aims to increase mining production. Our proposed system significantly enhances safety in the mining sector by leveraging advanced technology and innovative ideas.